STUDI EFEK PERMUKAAN SUBSTRAT ITO PADA PROSES DEPOSISI FILM DR-19 DENGAN METODE E-PVD - Haryati Lalo; Satyano Mongan; Patricia Silangen (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
Molecules and polymers with a conjugated chain structure such as the organic molecule Disperse Red-19 (DR-19) have delocalized π-electrons along the conjugation chain of the molecule and are easily moved by external electric fields, so that these materials have a large electrical polarizability and exhibit an optical response. which is quite high and very fast. This research was conducted with the aim of studying the surface effect of the Indium Tin Oxide (ITO) substrate in regulating the molecular orientation of the DR-19 film and the effect of the external electric field (E =1.9 MV/m) in regulating the molecular orientation of the DR-19 film. The fabrication method used is the E-PVD method, namely the PVD (Physical Vapor Deposition) method assisted by an external electric field. ) and the electric field E = 1.9 MV/m. The films were analyzed and characterized using X-ray diffraction spectroscopy (XRD). The XRD characterization results showed that with the help of an external electric field of 1.9 MV / m, the resulting film showed an increased structural order, marked by the formation of a crystalline structure in the DR-19 film. The E-PVD method (PVD method assisted by an external electric field E) is very effective in arranging DR-19 molecules so that the molecules can be arranged in an orderly parallel perpendicular to the surface of the ITO substrate.